Electrically switchable polypyrrole film for the tunable release of progesterone. (March 2013) - Svirskis, Darren; Sharma, Manisha; Yu, Yang; Garg, Sanjay
Background: Intrinsically conducting polymers, such as polypyrrole (PPy), have been utilized for drug delivery purposes as drug release rates can be tuned by electrical stimulation. Electrical stimulation can be used to switch the redox state of PPy, subsequently changing the electrostatic charge and volume of the polymer. Most literature to date has focused on the delivery of charged bioactives. This study aimed to prepare a PPy film formulation where the release rate of the uncharged drug progesterone could be electrically tuned.Results & discussion: In this study PPy films loaded with progesterone are described. Drug loading levels were influenced by the concentration of drug during manufacture and polymerization time. The polymer formulation was electrically conductive and electroactive, switchable between oxidized and reduced states. Drug release was influenced by the application of electrical stimulation, the greatest release was observed on application of +0.8 V (to oxidize the polymer). Triggered release was observed in response to a period of electrical stimulation (±0.8 V at 0.5 Hz).Conclusion: This study describes the preparation of a PPy film loaded with the uncharged drug progesterone. The release rate could be tuned with electrical stimulation.